2017
DOI: 10.1038/s41598-017-16355-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of low dose alteplase for intravenous thrombolysis in Asian stroke patients: a meta-analysis

Abstract: Whether low dose alteplase is comparable to standard dose in efficacy and safety for intravenous thrombolysis (IVT) in Asian stroke patients remains unverified. PubMed, EMBASE, and Cochrane Library Database from the beginning to June 30, 2017 were searched. IVT efficacy was measured by favorable outcome (modified Rankin Scale scores of 0–1) at 3 months, and safety measured by mortality within 3 months and symptomatic intracerebral hemorrhage (SICH). Pooled estimates were conducted using fixed- or random-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Supplementary Table 3 illustrates studies comparing low dose vs standard dose which mostly shows no difference for efficacy outcomes. A previous meta-analysis had concluded that there is no association between alteplase dose and favourable outcome and mortality, but that the low dose may be associated with a lower incidence of sICH [ 33 ]. From a cost perspective, alteplase used in Sri Lanka is made in India and a 20 mg vial costs USD 355 while a 50 mg vial costs USD 692.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Table 3 illustrates studies comparing low dose vs standard dose which mostly shows no difference for efficacy outcomes. A previous meta-analysis had concluded that there is no association between alteplase dose and favourable outcome and mortality, but that the low dose may be associated with a lower incidence of sICH [ 33 ]. From a cost perspective, alteplase used in Sri Lanka is made in India and a 20 mg vial costs USD 355 while a 50 mg vial costs USD 692.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary table 3 illustrates studies comparing low dose vs standard dose which mostly shows no difference for e cacy and safety outcomes. A previous meta-analysis had concluded that there is no association between alteplase dose and favourable outcome and mortality, but that the low dose may be associated with a lower incidence of sICH 44 . From a cost perspective, alteplase used in Sri Lanka is made in India and a 20 mg vial costs USD 355 while a 50 mg vial costs USD 692.…”
Section: Discussionmentioning
confidence: 99%
“…The early treatment of the thrombolytic after ischemic stroke (best time: 3-4.5 h) leads to the improvement of the positive effects of treatment and disability induced by the ischemic stroke (19). According to the literature, it is necessary to monitor the patient precisely from the injection to at least 48 h after treatment to reduce the side effects of TPA injection (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%